Anatomic, morphometric and histological features of glandula uropygialis in aseel roosters and hens - Bestami Yılmaz; İsmail Şah Harem; İsmail Demircioğlu; Gülsüm Özyiğit; Faruk Bozkaya (Eurasian Journal of Veterinary Sciences)
Aim: The present study was conducted to analyze the anatomic, morphometric and histological structure of the glandula uropygialis in Aseel roosters and hens. Materials and Methods: In the study, a total of 8 (4 males, 4 females) glandula uropygialis belonging to adult Aseel hens and roosters were used. Topographic features of the glandula uropygialis were analyzed in situ. The morphometric measurements were conducted on the dissected glands. Trichrome staining method was used to determine the histological structure of the glands, and Periodic Acid-Shiff (PAS) staining techniques were implemented to determine the glycogen and neutral mucins in the glands. Results: It was found out that the glandula uropygialis was topographically located on the cauda base, between the fourth caudal vertebrae and pygostyl. In terms of morphometric parameters, there were no statistically significant differences between hens and roosters or right and left lobes. Histologically, it was found that the secretoric tubules forming the parenchyma of the gland were separated from each other by connective tissue and showed a radial arrangement beginning from periphery and ending at the central cavity. Conclusion: It was concluded that the histological and anatomical structure of the glandula uropygialis in Aseel roosters and hens showed considerable similarities with that reported in other birds species.